HYPOGLYCEMIA IN PATIENT WITH CHRONIC KIDNEY DISEASE - Gabriela Medek (Revista de la Sociedad Argentina de Diabetes, 2018)
The strict blood glucose monitoring has proved to reduce the in- cidence and progression of chronic complications, with the resul- ting increase of hypoglycemia risk. At present, the American Association of Diabetes classifies: Level 1: warning of hypoglycemia <70 mg/dl; Level 2: clinically significant hypoglycemia <54 mg/ dl; Level 3: severe hypoglycemia, in which without specifying the value of glycemia, it is necessary the help of third parties or cognitive alterations appear. Hypoglycemia is usually less frequent  in patients with type 2 diabetes rather than type 1 diabetes; it is associated with the high morbidity and mortality, representing frequently one of the principal barriers to attain an optimal glycemia control. Patients with reduced glomerular filtration (GF) (<60 ml/min/1.73 m2) frequently present less insulin requirements and decrease of insulin degradation in peripheral tissue, which are risk factors for the development of severe hypoglycemia.